ON THE OBJECT OF EPISTEMOLOGY AS AN ACADEMIC RESEARCH PROGRAMME - Etorobong Godwin Akpan (Universitas PGRI Madiun, 2022)
The paper focuses on investigation of the object of epistemology as a research programme. It is warranted by the existence of programmes with incompatible objects in the history of philosophy that claim to be pursuing the same epistemic research objective. The purpose of the study is to identify and define a unifying object for epistemology in the midst of diverse alternatives. The method adopted for the study is content analysis. It was discovered that epistemology, which is a negation of skepticism, because it presupposes the possibility of knowledge, seeks as its object the discovery and characterization of the grounds upon which legitimate knowledge could be founded